Acetaminophen alleviates ferroptosis in mice with sepsis-associated encephalopathy via the GPX4 pathway. (6th October 2022) - Chu, Jing; Jiang, Yi; Zhou, Wenyu; Zhang, Jialei; Li, Hong; Yu, Yang; Yu, Yonghao
Sepsis-associated encephalopathy (SAE) is a cognitive impairment caused by sepsis, associated with increased morbidity and death. And acetaminophen (APAP) is a promising therapeutic medicine for SAE treatment. This research was designed to determine whether APAP alleviates SAE by attenuating ferroptosis and mediating the glutathione peroxidase (GPX4) pathway. The cecal ligation and puncture (CLP) approach was used to establish septic mouse models. The survival rates for 7 days were determined. The Morris water maze (MWM) was utilized to assess cognitive function. Hematoxylin and eosin (HE) staining identified histopathologic alterations in hippocampal tissue. Mitochondrial damage was discovered in hippocampal tissue using transmission electron microscopy (TEM). The reactive oxygen (ROS) levels in hippocampal tissue were measured using commercial assays. Septic cell models were produced using HT22 cells grown with 1 μg/ml lipopolysaccharide (LPS). ROS were quantified using immunofluorescence. Ferroptosis-related protein expression levels in hippocampal tissue and HT22 cells were measured using western blotting. To evaluate the iron content of hippocampal tissue and HT22 cells, commercial kits were employed. According to the findings, APAP improved survival rates, lowered hippocampal and mitochondrial damage, and improve cognitive impairment. In both animal and cell studies, APAP reduced iron content, ROS, glutamate antiporter (xCT), 4-hydroxy-2-nonenal (4-HNE) levels but increased GPX4 expression. However, RSL3, a GPX4 inhibitor that acts as a ferroptosis activator, decreased the protective properties of APAP in vitro . Our findings suggest that APAP reduces sepsis-induced cognitive impairment by reducing ferroptosis, which is mediated by the GPX4 signaling pathway.